Hubungan Agama dan Negara Perspektif Politik Islam: Kajian terhadap Implementasi dan Dampaknya dalam Ketatanegaraan Indonesia - Andi Ummung Magfira; Lara Indira Azzahra; Kurniati Kurniati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the relationship between religion and the state from the perspective of Islamic political thought and its implementation within Indonesia's constitutional system. The study aims to explain the fundamental principles, forms of implementation, and implications of the relationship between religion and the state in Indonesia's national and state life. The research employed a qualitative library research method by reviewing various sources, including books, scientific articles, academic journals, and relevant laws and regulations related to the research topic. The findings indicate that, from the perspective of Islamic political thought, the relationship between religion and the state is based on the concept of tawhid, which recognizes Allah as the ultimate source of values and law, while affirming the role of human beings as khalifah responsible for promoting justice, public welfare, and societal prosperity. In the Indonesian context, this relationship is implemented in an integrative manner through Pancasila and the 1945 Constitution of the Republic of Indonesia as the foundation of national and state life that upholds religious values while preserving diversity. The relationship between religion and the state contributes positively by strengthening morality, ethics, and social stability. However, it also has the potential to generate the politicization of religion, intolerance, and conflict if not managed wisely. Therefore, strengthening religious moderation, ensuring fair law enforcement, and promoting education that fosters the values of tolerance are essential to achieving a harmonious, democratic, and just society.